A multisite longitudinal evaluation of patient characteristics associated with a poor response to non-surgical multidisciplinary management of low back pain in an advanced practice physiotherapist-led tertiary service - Shaun O’Leary (BMC Musculoskeletal Disorders, 2020)
Abstract Background Non-surgical multidisciplinary management is often the first pathway of care for patients with chronic low back pain (LBP). This study explores if patient characteristics recorded at the initial service examination have an association with a poor response to this pathway of care in an advanced practice physiotherapist-led tertiary service. Methods Two hundred and forty nine patients undergoing non-surgical multidisciplinary management for their LBP across 8 tertiary public hospitals in Queensland, Australia participated in this prospective longitudinal study. Generalised linear models (logistic family) examined the relationship between patient characteristics and a poor response at 6 months follow-up using a Global Rating of Change measure. Results Overall 79 of the 178 (44%) patients completing the Global Rating of Change measure (28.5% loss to follow-up) reported a poor outcome. Patient characteristics retained in the final model associated with a poor response included lower Formal Education Level (ie did not complete school) (Odds Ratio (OR (95% confidence interval)) (2.67 (1.17–6.09), p = 0.02) and higher self-reported back disability (measured with the Oswestry Disability Index) (OR 1.33 (1.01–1.77) per 10/100 point score increase, p = 0.046). Conclusions A low level of formal education and high level of self-reported back disability may be associated with a poor response to non-surgical multidisciplinary management of LBP in tertiary care. Patients with these characteristics may need greater assistance with regard to their comprehension of health information, and judicious monitoring of their response to facilitate timely alternative care if no benefits are attained.